Chapter 11 – Competing with predators: multispecies and stakeholder interactions in fluctuating environments - Santos, Jorge (Septentrio Educational, 2015)
QUESTIONS ASKED How does the climate influence a fishery? How to conciliate the interests of predators? How to conciliate the interests of different industries? Corrumane dam ecosystem Mono Corrumane dam ecosystem Multi